P347 Does HPV vaccine initiation influence sexual behaviour? findings from the second australian study of health and relationships. (14th July 2019) - Yeung, Anna; Grulich, Andrew; Richters, Juliet; Visser, Richard De; Guy, Rebecca; Rissel, Chris; Simpson, Judy
Abstract : Background: In 2007, a national school-based vaccination program for human papillomavirus (HPV) among 12–13-year-olds was introduced in Australia, as well as a catch-up program for women aged ≤26. We examined associations between vaccine initiation and sexual activity to address concerns among some members of society that vaccination implies approval for sexual activity and could lead to early or risky sexual behaviour. Methods: Computer-assisted telephone interviews were conducted with a random sample of the Australian population aged 16–69 years during 2012–2013. Participants were surveyed about their sexual behaviour and HPV vaccine initiation. We restricted to women aged 16–20 years at the time of interview who would have been eligible for school-based vaccination. Responses were weighted based on study design, location, and the age-sex distribution of Australia. We used Pearson's chi-square tests and logistic regression to look at vaccine initiation and sexual behaviour, and report results as odds ratios (OR) and 95% Confidence Intervals (CI). Results: Among 920 women aged 16–20, 76.7% had initiated the vaccine. Proportions were higher among women born in Australia (81.2% versus 49.2% oversea-born, p<0.001), and who reported any sexual experience (84.7% versus 69.9% with no sexual experience; p<0.01). After adjusting for age, there was no association between vaccine initiation and any sexual activity before 16 years (early sexual behaviour) (OR=1.40; 95% CI: 0.63–3.13; p=0.41), or ever being diagnosed with an STI (OR=1.73; 95% CI: 0.38–7.86; p=0.48). Those initiating the vaccine were more likely to have had more than one partner in the last year (OR=2.31; 95% CI: 1.09–4.88;p=0.03) but this effect was attenuated after adjusting for age, rurality, religiosity, education, overseas-born, and income level (OR=1.69; 95% CI: 0.74–3.86;p=0.21). Conclusion: Differences in sexual activity between vaccinated and unvaccinated women were explained by confounding by characteristics such as age, overseas-born and income level. We found no evidence of an independent association between initiating the HPV vaccine and high-risk or early sexual behaviour. Disclosure: No significant relationships.